Pengenalan Pembelajaran Berbasis Game Edukatif untuk Meningkatkan Kemampuan Numerasi di SDN 39 Mataram - Lestari, Dewi Wulan; Khaerunnisa, Heni; Fu’adah, Yayu Fitriyatul; Hisda, Laylatul; Wulan, LL.Gede Damar (Rengganis Jurnal Pengabdian Masyarakat, 2024)
Characteristics of Indonesian students tend to easily get bored when learning with monotonous methods such as lecturing, especially in mathematics education. Students tend to comprehend learning materials more easily through interactive media combined with educational games. Implementing mathematics learning through educational games makes students happier and less prone to boredom, thereby motivating them to study more diligently. This Community Service project aims to determine the effectiveness of educational game-based learning on elementary school students' numeracy abilities. The project employs a quantitative descriptive research method with a sample of 12 elementary school students. Data collection involved pre-tests and post-tests comprising a total of 20 mathematics numeracy questions. Data analysis was conducted using Excel and SPSS software. The results indicate that educational game-based learning is effective in enhancing elementary school students' numeracy abilities, with an average effectiveness score of 38%, categorized as moderate.